Invasive aspergillosis in coronavirus disease 2019: a practical approach for clinicians. Issue 2 (3rd April 2022) - Lamoth, Frederic
Abstract : Purpose of review: Invasive pulmonary aspergillosis (IPA) can affect patients with severe coronavirus disease 2019 (COVID-19), but many questions remain open about its very variable incidence across the world, the actual link between the viral infection and the fungal superinfection, the significance of Aspergillus recovery in a respiratory sample, and the management of such cases. This review addresses these questions and aims at providing some clues for the practical diagnostic and therapeutic approaches of COVID-19-associated pulmonary aspergillosis (CAPA) in a clinical perspective. Recent findings: Definitions have been proposed for possible/probable/proven CAPA, but distinction between colonization and invasive fungal infection is difficult and not possible in most cases in the absence of histopathological proof or positive galactomannan in serum. Most importantly, the recovery of an Aspergillus by a direct (culture, PCR) or indirect (galactomannan) test in a respiratory sample is an indicator of worse outcome, which justifies a screening for early detection and initiation of preemptive antifungal therapy in such cases. Summary: The COVID-19 pandemic has increased our awareness of IPA among ICU patients. Although current recommendations are mainly based on experts' opinions, prospective studies are needed to get more evidence-based support for the diagnostic approach and management of CAPA.